ENHANCING ACCOUNTING INFORMATION SYSTEMS: THE ROLE OF CLOUD ACCOUNTING AND TECHNOLOGY IN HOSPITALITY - Natalia Hakimi; Fatin Syazwani Safiyuddin; Erma Shahida Kaap; Ija Hazirah Nur Rosni; Liyana Nadhirah Kamal (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Cloud accounting and technology advances have had a significant impact on the quality of accounting information systems, particularly in the hospitality industry. The integration of cloud accounting into accounting practices has enabled faster and more efficient data processing, leading to increased accuracy and improved operational performance. Furthermore, technology advances have contributed to the development of cloud-based accounting systems, which provide enhanced decision-making capabilities and contribute to higher-quality information systems. These advancements have been instrumental in promoting cost-effectiveness for firms and enhancing firm performance through digital transformation and digital leadership. This study explores the influence of cloud accounting and technological advancements on the quality of accounting information systems within the hospitality industry. With the rapid evolution of technology, cloud accounting has emerged as a transformative tool for enhancing data management and processing capabilities in various sectors. Through a quantitative data analysis, this study aims to provide valuable insights into the evolving landscape of accounting information systems in the hospitality industry in response to cloud accounting and technological advancements. The findings of the study on the effect of cloud accounting and technology advances on the quality of accounting information systems within the hospitality industry have significant contributions towards regulators as they can enhance the policy, government to improve on their decision making, as well as educators to develop curricula that focus on the importance of technology in accounting practices.